PENGEMBANGAN DESAIN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITES KEPADA GURU PADA PEMBELAJARAN DARING DI SMP ISLAM HARAPAN IBU JAKARTA-SELATAN - Setiawan, Kukuh; Nomi, Ahmad Suryadi; Winata, Widia (Universitas Muhammadiyah Jakarta, 2022)
ABSTRACTGoogle sites is one of the web site media that can be used in the learning process, group or personal. The purpose of this study is to find out: 1) Develop a design of learning media based on google sites in online learning, 2) How is the feasibility of designing learning media based on google sites in online learning. 3) How effective is the design of learning media based on google sites in online learning. 4) What is the potential effect of using google sites-based learning media design on online learning. The research approach used in this research is Research and Development (RnD). The results of this study are the development of online learning based on Google Sites based on the ADDIE model and declared